Erotismo e contemplação em Infância , de Manoel de Barros - Figueiredo, Marina Haber de (2011)
This research proposes to examine the texts ―Obrar‖, ―Ver‖, ―O apanhador de desperdício‖, ―Achadouros‖, ―Sobre importâncias‖ and ―Soberania‖ tha are present, respectively, on the books Memórias Inventadas: A Infância, Memórias Inventadas: A Segunda Infância, Memórias Inventadas: A Terceira Infância, published in 2003, 2006 and 2008 and written by Manoel de Barros, because we start from the premise that the aesthetic discourse of the subjects of these texts represents Barros s architectonics when he works with a construction of a discourses that are opposite of the contemporary social-political system discourses, that´s because while this hegemonic discourse, with its exclusionary and accumulative logic, disseminates a respect to the cartesian and logical world represented by the world of labor, that are the construction of opposite discourses expressed by the subjects of the above texts, which proclaim the world by an optic that values concrete subjectivism and, at the same time, contemplative and erotic, represented by the view and the voice of an adult-child subject, in its childhood. This way, we intend to show the aesthetic construction of these discourses, by a bakhtinian analysis about the subjects, time and space. The theoretical-analytical notions studied by the Bakhtin s Circle (that means the writings by Bakhtin, Voloshinov and Medvedev) are the basic proposals of this research (specifically the dialogism - as a philosophic notion focused on the Russian circle - ethics and aesthetics, subject, chronotope and carnavalization), since they collaborate for a better comprehension around the constitution of the aesthetic discourse proposed by Barros. This way of seeing, understanding and reprsentating the world achieves a new aesthetic meaning which undervalues the sense of speed and accuracy of the "adult world", present in this hegemonic discourse, to turn it into lightness, eroticism and contemplation, that are trangressors and constituentes values of early childhood memories of the ―adult-child‖ subject, ―porque eu não sou da informática: eu sou da invencionática (Barros, 2003, IX).